How Grit is Related to Objectively Measured Moderate-to-Vigorous Physical Activity in School Student - Vello Hein; Hanna Kalajas-Tilga; Andre Koka; Lennart Raudsepp; Henri Tilga (Montenegrin Sports Academy, 2019)
This study aimed to estimate parameters of the model in which perseverance of effort and consistency of interest of grit scale are related directly to objectively measured physical activity (PA) and indirectly via PA intention in school students (N = 209) aged 12 to 14 years. The Grit Scale was used to estimate the consistency of interests and perseverance of efforts. The measure for intention consisted of two items from the Theory of Planned Behaviour Questionnaire. Actigraph was used to measure moderate-to-vigorous physical activity (MVPA) during seven consecutive days. A well-fitting structural equation model (χ2 = 46.169, df = 31; CFI = .958; RMSEA = .053) demonstrated the significant direct effect (β = .286, p< .001) from perseverance of efforts on intention to be physical active. Physical activity intention mediated the effect of the perseverance of efforts on moderate-to-vigorous physical activity (MVPA), but not the effect of consistency of interest. The total effect from the consistency of interest on MVPA was significant, but the perseverance of efforts was not. The dimension of the perseverance of efforts between groups with high and low MVPA was not statistically significantly different, whereas the intention was significantly higher in the high-MVPA group. The consistency of the interest dimension in the high MVPA group was significantly higher than in low group only at p < .1 level. The findings of the study may be used by physical education teachers for the promotion of physical activity, highlighting the role of consistency of interest on MVPA.